2018
DOI: 10.5723/kjcs.2018.39.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Profiles and Children's Social Skills: The Mediating Role of Effortful Control

Abstract: Objective: The present study examined the direct and indirect effects of mother's distinct parenting profiles on the development of children's social skills, mediated by the children's effortful control. Methods: Maternal parenting styles were measured by a self-rated questionnaire. Children's effortful control was assessed using behavioral tasks, namely the Red-Green Sign task and the Head-Toes-Knees-Shoulders task. Children's social skills were measured through a teacher-rated questionnaire. Results: Latent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…In particular, in the case of mothers of school-age children, the characteristics of controlling parenting behavior scored high in comparison to other types of attitudes. This result is similar to the result of a parenting attitude study of Korean mothers [ 40 ], in which the firm and strict parenting type accounted for the highest proportion at 39.4%. It is also similar to the result of a parenting style study of Chinese mothers [ 41 ], in which Chinese mothers showed a high level of controlling behavior.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, in the case of mothers of school-age children, the characteristics of controlling parenting behavior scored high in comparison to other types of attitudes. This result is similar to the result of a parenting attitude study of Korean mothers [ 40 ], in which the firm and strict parenting type accounted for the highest proportion at 39.4%. It is also similar to the result of a parenting style study of Chinese mothers [ 41 ], in which Chinese mothers showed a high level of controlling behavior.…”
Section: Discussionsupporting
confidence: 88%
“…3 --- (McClelland et al, 2007) . , (Koo & Park, 2018). 19 Interaction Effect of Empathy and Effortful Control .…”
Section: 유아의 공감능력 검사 도구mentioning
confidence: 99%